Financial crises and venture capital development: evidence from Indonesia. Issue 1 (1st January 2019) - Lingelbach, David
ABSTRACT: This exploratory study examines how financial crises impede or support venture capital (VC) development in the context of Indonesia and the 1997–1998 Asian financial crisis (AFC). Using a mixed-methods research methodology, the study finds that financial crises have divergent effects on VC development. Financial crises support VC development through accelerated VC practise diffusion, but impede that development by slowing VC enabling conditions. The effects of the substantial macro institutional changes often associated with financial crises are insufficient to overcome these impediments, resulting in a smaller VC industry.